TEACHERS' AND STUDENTS' PERCEPTIONS OF TECHNOLOGY IN EDUCATION - Widodo, Jordy Satria; Parwanto, Novia Budi; Ragamustari, Safendrri Komara (Institute of Advanced Engineering and Science, 2020)
This study focuses on elucidation of the perception of actors in education toward the use of technology in the 2013 Indonesian Education Curriculum (C-13). The study was done at SMA Plus YPHB and SMAN 4 Bogor, high schools located in Bogor City, West Java, Indonesia. The specific policy that underlies this study is the Regulation of Ministry of Education and Culture No.70/2013 in the point of completion mindsets No. 6 about the shift from single tool learning to multimedia-tool based learning. This paper integrates mixed methods?qualitative and quantitative methods, which use questionnaires and interview by incorporating Extended Technology Acceptance Model (TAM) using path regression analyses. The subjects of the research are teachers and students in the schools, an education practitioner, and an educational policy advisor. Furthermore, the assessment was done toward the perceptions of educational technology infrastructure, such as computers/laptops, projectors, speaker, Internet, software application and mobiles. The results show that Perceived Usefulness (PU) is better shaped by Perceived Ease of Use (PEU), Attitude Toward Using (ATU) is influenced by PEU, and Intention to Use (IU) is significantly affected by ATU. However, the external variables are novel for teachers and students. For teachers, the external variables do not determine PU, yet age influences PU for students. Thus, teachers and students show good intention to use the technology providing they embrace positive attitudes in using it.